Tonga resumes exports in the region - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
A total of 17 agricultural products from Tonga have been approved for export to American Samoa, Fiji, and Niue after the ban on these products had been lifted. The ban was imposed to prevent pests from entering other islands. The approved produce...